Association of endothelial nitric oxyde synthase (eNOS) levels and modifiable risk factors for acute myocardial infarction with ST-segment elevation (AMI-STE) - Leona, Denada Florencia; Syafri, Masrul (Jurnal Ilmu Kesehatan dan Kesehatan, 2024)
Background. The pathological process underlying myocardial infarction is atherosclerotic thrombosis that causes endothelial dysfunction. In the AMI-STE process, eNOS has functions as the body's defense mechanism to prevent more severe damage to the endothelium. Decreased eNOS levels were found in modifiable AMI risk factors. This study aimed to determine the association of eNOS levels based on modifiable risk factors for AMI-STE patients. Method. This study was an analytical observational study with a historical cohort design. The samples were patients with AMI-STE diagnosis who had undergone PPCI at M. Djamil Hospital Padang from March to June 2022. The eNOS levels were taken from the blood samples. Modifiable AMI risk factors were taken from patient’s medical record. The T test was carried out to determine statistical analysis. Results. The average age of the 38 subjects was 62.53 ± 8.2 years, and 92.1% among them were male, and 52.6% subjects were diagnosed with anterior AMI-STE. The average eNOS level in subjects was 47.47 ± 23.88 (normal level is 48.16 pg/mL). More than half (73.5%) of the subjects in low eNOS group had diabetes mellitus as risk factor (P<0.0001) and most subjects (78.9%) in group with low eNOS had hypertension (p=0.022). Other risk factors, namely dyslipidemia and smoking, were also more common in group with low eNOS. However, statistical tests showed that there was no statistically association between eNOS levels with dyslipidemia and smoking. Conclusion. There was statistically significant association between eNOS levels with diabetes mellitus and hypertension as modifiable risk factors for AMI-STE.